ReactorAFM/STM – dynamic reactions on surfaces at elevated temperature and atmospheric pressure - Roorda, Tycho; Achour, Hamed; van Spronsen, Matthijs A.; Cañas-Ventura, Marta E.; Roobol, Sander B.; Onderwaater, Willem; Bergman, Mirthe; van der Tuijn, Peter; van Baarle, Gertjan; Bakker, Johan W.; Frenken, Joost W. M.; Groot, Irene M. N. (Beilstein Journal of Nanotechnology, 2025)
Previous work has shown the ReactorSTM and ReactorAFM, capable of studying materials under industrially relevant conditions. Here we show current developments of the ReactorAFM/STM, implementing a qPlus sensor to add the ability of combining atomic force microscopy (AFM) and scanning tunneling microscopy (STM) techniques to study the geometric and electronic structure of materials under reaction conditions. We demonstrate this by imaging a Pd(100) single crystal at 450 K with combined AFM/STM. The surface is compared under ultrahigh vacuum and under 0.5 bar O2 pressure showing a notable increase in RMS current, which we attribute to oxidation. Also, we study cobalt nanoparticle catalysts on an aluminum oxide support, industrially relevant in the Fischer–Tropsch synthesis. The catalysts are imaged before and after reaction at 430 K as the current maximum temperature of the qPlus sensor used falls just below the reaction temperature. Quadrupole mass spectrometry data show the reaction taking place by monitoring product gases during heating and cooling of the sample under CO and H2 gas pressures of 2 bar. The monitored gases include H2O as byproduct and the hydrocarbons ethane (m/z = 30), propane (m/z = 44), and hexane (m/z = 86), which all show increases in counts while between 490 and 550 K. The added ability to scan various surfaces with combined AFM/STM while monitoring the reaction products demonstrates the versatility offered by the ReactorAFM/STM to study catalysts under realistic industrial conditions.
Keywords: combined AFM/STM; conductive AFM; model catalysts; nc-AFM; operando catalysis; qPlus tuning fork sensor